2016
DOI: 10.1103/physreve.93.042707
|View full text |Cite
|
Sign up to set email alerts
|

Effective long-range interlayer interactions and electric-field-induced subphases in ferrielectric liquid crystals

Abstract: Microbeam resonant x-ray scattering experiments recently revealed the sequential emergence of electricfield-induced subphases (stable states) with exceptionally large unit cells consisting of 12 and 15 smectic layers. We explain the emergence of the field-induced subphases by the quasimolecular model based on the Emelyanenko-Osipov long-range interlayer interactions (LRILIs) together with our primitive way of understanding the frustration in clinicity using the q E number defined asand [L] refer to the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…proposed by Chandani et al [35] under an electric field is the same as the present one, but those authors concluded that the "q E n = 3" model was difficult to be stabilized from the free-energy density point of view. Furthermore, the sequential phase transition, i.e.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…proposed by Chandani et al [35] under an electric field is the same as the present one, but those authors concluded that the "q E n = 3" model was difficult to be stabilized from the free-energy density point of view. Furthermore, the sequential phase transition, i.e.…”
Section: Discussionsupporting
confidence: 61%
“…21), where only the two peaks at q/q o = 4/9 and 5/9 are strong. The other two calculations [35,36] discussed the possibility of the {R 3 (R 2 L) 2 } configuration, i.e. the same as the present one.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…From geometrical conditions, the practical q/q 0 resolution of the measurement was less than 0.005, though it depended on the counting statistics in practice. Finally, the RXS intensity in the present experiment was mainly due to σπ scattering (π incident and σ scattered X-rays) because the incident beam was π polarized with respect to the reflection plane in our experimental arrangement and that the RXS theory predicts that the contribution from ππ scattering is very weak [40].…”
Section: Methodsmentioning
confidence: 51%
“…Chandani et al [40], the C 6p {R 5 L} structure appeared as one of the possible configurations in the electric-field induced phase transition. The superlattice structures recently proposed [47] might coincide with our transitional subphases (q E = 1/2 and 3/5 for C 4p2 and C 5p , respectively), though the sample, the experimental conditions were different from our experiments.…”
Section: Figs 13 (A) To (C) Shows the Satellite Reflection Intensitimentioning
confidence: 99%